Mars atmospheric entry guidance for optimal terminal altitude. (February 2019) - Long, Jiateng; Gao, Ai; Cui, Pingyuan; Liu, Yang
Abstract: Maximizing the terminal altitude for Mars atmospheric entry has long been investigated on trajectory design to allow a sufficient timeline margin for subsequent operations and the scientific requirements of exploring Mars ancient highland. The purpose of this paper is to design an onboard Mars atmospheric entry guidance algorithm, which can achieve the optimal terminal altitude at the predetermined terminal flight range. Two important characters that the optimal bank angle profile are revealed in this paper, offering the gateway to the application of the optimal guidance by onboard parameter searching, which will be accomplished by the numerical predictor-corrector strategy. Moreover, suboptimal situations are also investigated considering the performance restriction of reactive control system (RCS). Effectiveness of the proposed guidance algorithm is demonstrated using scenarios of the Mars Science Laboratory (MSL) mission. Highlights: Optimal guidance achieves terminal position accuracy and optimal terminal altitude. Two important characters that the optimal bank angle profile are revealed. The optimal guidance algorithm does not rely on offline trajectory optimization.